Comparision of a Glove-Based Dressing Regimen with Conventional Dressings in Treatment of Superficial Partial-Thickness and Small Deep-Dermal Hand Burns - Chalwade, Chandrashekhar Subhash; Teja, Mudunuri Ravi; Mago, Raghav; Sawant, Abhijeet D. (Indian Journal of Plastic Surgery, 2025)
In cases of burns affecting the hand, minimizing morbidity and disability is crucial. Early mobilization is essential to prevent persistent contractures and optimize functional outcomes by gradually improving range of motion. The purpose of this study was to determine the efficacy of a glove-based dressing regimen in treating superficial partial-thickness and small deep-dermal hand burns compared to conventional dressings.This study was conducted in a burn department affiliated with a tertiary care center over a period of 1 year between January 2018 and December 2018. A total of 75 digits (23 hands of 14 patients) were included in the study with 38 under a case group and 37 under a control group. The primary outcome of study was evaluated by assessing the edema, healing time, and mobility of the affected digit.Mean healing time in the case group was 12.4 days (range: 11–14, standard deviation [SD]: 0.992). The mean VAS (visual analog scale) score was 8.42 (range: 13–17, SD: 1.136). The percentage increase in mobility was 70.81% in the case group (glove dressing) as opposed to 46.57% in the control group (conventional dressing) at 10 days post-burn, which was statistically significant.Sterile glove dressing techniques can be handy and a convenient method for dressing of hand burn injuries.
Keywords: burn injuries; glove dressing; hand; digit mobility